Advanced glycation endproducts mediate chronic kidney injury with characteristic patterns in different stages - Huang, Xiaoxia; Li, Bingyu; Hu, Jiaqing; Liu, Zhuanhua; Li, Dongping; Chen, Zhenfeng; Huang, Hang; Chen, Yanjia; Guo, Xiaohua; Cui, Yun; Huang, Qiaobing (Frontiers in Physiology, 2022)
Advanced glycation endproducts (AGEs) have been confirmed to play a causative role in the development of diabetic nephropathy (DN). In this study, we revealed that AGEs induced kidney injury with characteristic patterns in different stages and moesin phosphorylation plays a role in these processes. In WT mice treated with AGE-modified bovine serum albumin (AGE-BSA), distinct abnormal angiogenesis in Bowman’s capsule of kidney emerged early after 1 m under AGE-BSA stimulation, while these neovessels became rare after 6 m. AGE-BSA also induced glomerular hypertrophy and mesangial expansion at 1 m, but glomerular atrophy and fibrosis at 6 m. Electron microscopy imaging demonstrated the damage of foot process integrity in podocytes and the uneven thickening of glomerular basement membrane in AGE-BSA-treated group, which was more significant after 6 m of AGE-BSA treatment than 1 m. The kidney dysfunction appeared along with those AGE-induced morphological changes. However, those AGE-BSA-induced pathological changes were significantly attenuated in RAGE knockout mice. Moreover, moesin phosphorylation was accompanied with those AGE-BSA-induced alterations and moesin deficiency in mice attenuated AGE-BSA-induced fibrosis. The investigation on glomerular endothelial cells (GECs) also confirmed that the phosphorylation of moesin T558 is critical in AGE-induced tube formation. Overall, this study suggests that AGEs mediate kidney injury with characteristic patterns by binding with RAGE and inducing moesin phosphorylation.